Orelabrutinib Combined With Lenalidomide and Immunochemotherapy for Relapsed/Refractory Primary Central Nervous System Lymphoma: A Retrospective Analysis of Case Series - Yang, Chuanwei; Cui, Yong; Ren, Xiaohui; Li, Ming; Yu, Kefu; Shen, Shaoping; Jiang, Haihui; Li, Mingxiao; Zhang, Xiaokang; Zhao, Xuzhe; Zhu, Qinghui; Lin, Song (Frontiers in Oncology, 2022)
Background: Relapsed/refractory (r/r) primary central nervous system lymphoma (PCNSL) is an intractable situation without sound treatment. Bruton’s tyrosine kinase (BTK) represents an attractive drug target in PCNSL. Orelabrutinib is a new-generation BTK inhibitor with high cerebrospinal fluid (CSF) concentration. This study aimed to evaluate the efficacy and safety of orelabrutinib-containing combination therapy in patients with r/r PCNSL. Methods: We retrospectively analyzed r/r PCNSL patients who received combination therapy with rituximab, high-dose methotrexate, temozolomide, orelabrutinib and lenalidomide, and further explored the relationship between the efficacy and genetic characteristics. Results: A total of fifteen patients were included in this retrospective study. The overall response rate (ORR) was 86.7%, the complete remission (CR) rate was 73.3% and the disease control rate (DCR) was 93.3%. Among 13 responders, 9 patients are still receiving oral orelabrutinib and lenalidomide. The most common adverse event (AEs) was transaminase increase (66.7%). No grade 4 AE or drug-related death was reported. Genomic sequencing showed that patients who responded to orelabrutinib had abnormal NF-κB activation, while those who had no response were mainly enriched with transcriptional misregulation. Patients who had mutations in TLR, BCR, or NF-κB pathway achieved complete or partial response to the orelabrutinib-containing therapy. Moreover, the blood and cerebrospinal fluid circulating tumor DNA (ctDNA) were closely associated with tumor recurrence and treatment response and sustained tumor responses correlated with the clearance of ctDNA. Conclusion: Orelabrutinib-containing regimen was effective and well-tolerated in patients with r/r PCNSL. Genome sequencing of tumor samples could help to screen patients who may respond to the orelabrutinib-containing regimen, and liquid biopsy may contribute to tracing tumor burden and monitoring treatment response.